PROOF OF ALGEBRAIC STRUCTURES (RINGS AND FIELDS) WITH JAVA PROGRAMMING - Ngarap Imanuel Manik; Deshinta Puspa Ayu Dwi Argaswari (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2023)
Many branches of algebraic structures, such as rings and fields, are difficult to comprehend and undesirable due to their abstract character. The testing of algebraic structures can be aided by a computer software application, which makes it simpler and more fun to learn algebraic structures. This program is expected to make algebraic structural proofing easier, faster, and more accurate than manual proof. Users and the software in the application are connected through the Cayley table. The Java programming is just used to demonstrate the algebraic structures of rings and fields. The application program's proof results for the subject showed correct results with a quick processing time when compared to manual processing.